Polyethylene-oxide: NaI polymer electrolyte: Electrical, structural and photoelectrochemical studies. (February 2023) - Singh, Abhimanyu; Joshi, Bhawana; Rawal, Sangeeta; Singh, Pramod K; Konwar, Subhrajit; Madkhli, Aysh Y; Noor, IM; Aggarwal, Daksh; Ibrahim, Summayya Saleh
Conducting sodium iodide (NaI) doped polyethylene oxide (PEO) freestanding electrolyte films are prepared by solution cast technique. Electrical, Structural, and device performances are given in detail. Maximum conducting polymer electrolyte has been used to develop electric double-layer capacitors (EDLCs) as well as the dye-sensitized solar cell (DSSC) which shows that ion-conducting polymer electrolyte is a novel candidate for energy devices.